Prospective impacts of expanding agroecological transitions on Zimbabwe’s government's socio-economic and environmental agendas - Mabhaudhi, Tafadzwanashe; Chimonyo, Vimbayi G.P.; Sobratee, Nafiisa; Sardeshpande, Mallika; Ngoma, Hambulo (CGIAR, 2024)
The CGIAR funded Agroecology Initiative (AE-I) in Zimbabwe aims to achieve specific outcomes that will contribute to the broader goal of promoting agroecology in diverse contexts in Zimbabwe by 2024. As AE-I gains a deeper understanding of agroecology in the context of its implementation sites in Zimbabwe, it has become clear that it must critically evaluate its incremental efforts viz their transformative capabilities per agroecological principles.Thus, the current assignment seeks to assess the extent to which AE-I’s activities impact the broader socioeconomic and environment agendas in Zimbabwe. The goal is to assess agroecological practices' early impacts and map transformative pathways to achieving broader systemic impact. This analysis will inform a scaling strategy for AE-I. Moreover, it will allow AE-I to navigate the complex relationship between agroecology and broader social-economic-ecological agendas. By conducting an ex-ante assessment, this assignment aims to determine the potential extent and impacts of agroecological transitions, as defined by the activities undertaken by AE-I, on government priorities and commitments, including key national benchmarks like the Nationally Determined Contributions (NDCs) and the National Biodiversity Strategy and Adaptation Plans (NBSAPs). Additionally, we recognize the importance of understanding the underlying dynamics shaping agroecological transitions. This involves analyzing the roles of agroecological science, practices, and social movements in influencing behavioral shifts and empowering smallholder farming households. By synthesizing insights from Zimbabwean experiences and AE -I activities, and integrating them into a strategic framework, we aim to facilitate the transition of farming households in low- and middle-income countries towards agroecology. This report details an ex-ante assessment to evaluate the prospective impacts of expanding agroecological transitions on government socio-economic and environmetal agendas, incorporating an analysis of national commitments like Nationally Determined Contributions (NDCs) and the National Biodiversity Strategy and Adaptation Plans (NBSAPs).